Ubiquinone-binding site mutagenesis reveals the role of mitochondrial complex II in cell death initiation - Kluckova, K; Sticha, M; Cerny, J; Mracek, T; Dong, L; Drahota, Zdeněk; Gottlieb, E; Neuzil, J; Rohlena, J (Cell death & disease, 2015)
Respiratory complex II (CII, succinate dehydrogenase, SDH) inhibition can induce cell death, but the mechanistic details need clarification. To elucidate the role of reactive oxygen species (ROS) formation upon the ubiquinone-binding (Qp) site blockade, we substituted CII subunit C (SDHC) residues lining the Qp site by site-directed mutagenesis. Cell lines carrying these mutations were characterized on the bases of CII activity and exposed to Qp site inhibitors MitoVES, thenoyltrifluoroacetone (TTFA) and Atpenin A5. We found that I56F and S68A SDHC variants, which support succinate-mediated respiration and maintain low intracellular succinate, were less efficiently inhibited by MitoVES than the wild-type (WT) variant. Importantly, associated ROS generation and cell death induction was also impaired, and cell death in the WT cells was malonate and catalase sensitive. In contrast, the S68A variant was much more susceptible to TTFA inhibition than the I56F variant or the WT CII, which was again reflected by enhanced ROS formation and increased malonate- and catalase-sensitive cell death induction. The R72C variant that accumulates intracellular succinate due to compromised CII activity was resistant to MitoVES and TTFA treatment and did not increase ROS, even though TTFA efficiently generated ROS at low succinate in mitochondria isolated from R72C cells. Similarly, the high-affinity Qp site inhibitor Atpenin A5 rapidly increased intracellular succinate in WT cells but did not induce ROS or cell death, unlike MitoVES and TTFA that upregulated succinate only moderately. These results demonstrate that cell death initiation upon CII inhibition depends on ROS and that the extent of cell death correlates with the potency of inhibition at the Qp site unless intracellular succinate is high. In addition, this validates the Qp site of CII as a target for cell death induction with relevance to cancer therapy.
Keywords: Electron Transport Complex II; Mitochondria; vazebná místa; ubichinon; molekulární sekvence - údaje; Amino Acid Sequence; mutageneze cílená; Cell Death; buněčná smrt; respirační komplex II; Mutagenesis, Site-Directed; Binding Sites; lidé; konformace proteinů; Humans; Ubiquinone; sekvence aminokyselin; Molecular Sequence Data; Protein Conformation; mitochondrie